UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG AKAR TUBA (Derris elliptica Benth) UNTUK MENGENDALIKAN HAMA PENGGEREK TONGKOL JAGUNG Helicoverpa armigera Hubn - Rudi Rismawanto; Rusli Rustam; Desita Salbiah (DINAMIKA PERTANIAN, 2022)
Pests that attack the corn crop are corn cobs borer (Helicoverpa armigera Hubner). Pest control can be done using tubal root vegetable insecticide (Derris elliptica benth.) This study aims to obtain the best concentration of tuba root powder extract for controlling the corncob borer pests Helicoverpa Armigera H. Research was carried out at the Plant Pest Laboratory of the Faculty of Agriculture, University of Riau. This study used a completely randomized design (CRD) with 6 treatments and 4 replications. The treatments were given several concentrations of tuba root powder extract, namely 0 gr.l-1 water, 20 gr.l-1 water, 40 gr.l-1 water, 60 gr.l-1 water, 80 gr.l-1 water and 100 gr.l-1 water. The parameters observed were initial death, lethal time of 50, lethal concentration of 50 and 95, daily mortality, and total mortality. Daily mortality data obtained from the results were analyzed descriptively and displayed in graphical form, data lethal concentration (LC50 and LC95) was used probit analysis using the POLO-PC program, while other data such as initial death, total mortality, and lethal time (LT50) were statistically analyzed using variance. Data from analysis of variance will be continued using the smallest significant difference (LSD) test at the 5% confident level. Application of concentration for tubal root extract 100 g-1 water was the best concentration to control larvae H. Armigera with an initial time of death 26.50 hours, LT50 67.50 hours, highest daily mortality on the fourth day by 40% and total larval mortality by 87.5%.